Campylobacter : a practical approach to the organism and its control in foods - Bell, C. , 1946-; Kyriakides, Alec (Practical food microbiology series, 2009)
Campylobacter is the most common cause of bacterial food poisoning with over 400 million cases worldwide reported each year.